Making sense of the past: The embodied information practices of field archaeologists. (June 2016) - Olsson, Michael
This paper reports the findings of a study of the information practices of archaeologists, students and volunteers undertaking an excavation in the field. Conceptually, the study was guided by a social constructionist and practice-theoretical epistemological standpoint. Methodologically, the study employed a multi-faceted approach incorporating both ethnographic observation of archaeologists working in the field and in-depth interviews. The findings show that participants' practices were both social and embodied in nature.